Identification and Efectiveness of Halal Tourism Laws in Indonesia - Susilawati, Cucu (Universitas Muhammadiyah Surakarta, 2023)
Indonesia has two crucial points in halal tourism: having a variety of attractive halal tourist destinations and a sizeable Muslim community. However, Indonesia still needs to improve compared to other countries. This study aimed to identify and determine the effectiveness of halal tourism regulations for Muslim communities in Indonesia. This research is normative empirical model in nature where several established rules and regulations are critically reviewed. A simple interview also conducted to support the result. This study found that the main umbrella of regulation was Law number 33/2014 on Halal Product Guarantee and Islamic Guidance of DSN-MUI Fatwa 108/DSNMUI/X/2016 on Toursim Management Based on Islamic Principles. While the latter is not a binding rule, the initial was found to be ineffective altough fulfilled the Rule of Law. In addition to that factor, we also found the ineffectiveness of law enforcement, the lacking facilities and inadequate infrastructure and low public awareness on the regulation. This article suggested that Indonesia should enact a more specific law devised for halal tourism to ensure the accelaration of this fast growing industry.